(untitled) (International Journal of Engineering and Computer Science, 2017)
A distributed system is a collection of independent computers that appears to its user a single coherent system. This definition can explain several important aspects. The first fact is that a distributed system is the collection of different types of component’s for example computer, networking devices, storage, printers etc. In this paper we presented a detailed review of all the scheduling technique used by Hadoop framework this paper provides you deep insight of these scheduler working.